Comparison of quiet time vertical plasma drifts with global empirical models over the Indian sector: Some insights. (May 2017) - Pandey, Kuldeep; Sekar, R.; Gupta, S.P.; Chakrabarty, D.; Anandarao, B.G.
Abstract: The threshold vertical plasma drifts and their polarities are inferred from E-region irregularities reported earlier using different experiments conducted from India during geomagnetically quiet time. In addition, the hourly variations of magnetometer data sets are used in conjunction with an equatorial electrojet model (Anandarao, 1976) to deduce the vertical drifts around noon time (10:00–140:00 LT ). These results are then compared with the vertical drifts presented by empirical models (Scherliess and Fejer, 1999; Fejer et al., 2008a) corresponding to the 60 ° E longitude sector. In general, the vertical drifts presented by empirical models are consistent with those inferred from snapshot measurements of E-region irregularities at different local times of the day except around sunrise hours. Further, the vertical drifts presented by Fejer et al. (2008a) model match fairly well with seasonally averaged vertical drifts deduced (within 1 σ variation) using magnetometer data. A time difference is noticed between occurrence of pre-reversal enhancement in vertical drifts over India reported earlier using different techniques and Scherliess and Fejer (1999) model. Probable reason for the time difference is discussed. The occurrence characteristic of afternoon equatorial counter electrojet in June solstice during low solar epoch is consistent with the drifts obtained from empirical models. The seasonally averaged vertical drifts during nighttime reported earlier using ionosonde/HF radar experiments are not consistent with the presence of streaming plasma waves on a few occasions. Further, nocturnal vertical drifts are systematically under-estimated and probable reason for this is discussed. Highlights: Vertical drifts from two global empirical models are compared with Indian measurements. Fejer et al. (2008a) model seems to agree better with Indian measurements. Probable reasons for differences between models and measurements are discussed.